Pedagogical Frameworks for The Development of Information and Analytical Competence in Future History Teachers Based on History Education - Siddiqov Ilyosjon Baxromovich (Scientific Trends, 2023)
In this article, the teaching method of teaching historical sources and manuals, historical and artistic works, history in the development of information and analytical competence of future history teachers and a practical method of teaching history, traveling vertically in history, studying historical history based on seeing, cultivating knowledge, skills and skills, developing the worldview scientific and methodological sources on the problems of teaching history have been analyzed.
Keywords: teaching history, future history teachers, information and analytical competence, history education, historical sources, historical and artistic works, scientific-methodological approach, exhibition education, excursion, expedition, vertual museums, vertual historical travel.